Perceptions of HIV-related trauma in people living with HIV in Zimbabwe's Friendship Bench Program: A qualitative analysis of counselors' and clients' experiences. (February 2020) - Verhey, Ruth; Chibanda, Dixon; Vera, Aquila; Manda, Ethel; Brakarsh, Jonathan; Seedat, Soraya
This study investigated the experience of lay health workers (LHWs) delivering problem-solving therapy (PST) for common mental disorders (CMD) as well as clients' views of the PST program referred to as the Friendship Bench (FB). Semi-structured interviews were conducted with LHWs (n = 5) and clients living with HIV (PLWH) (n = 10). Data were analyzed using thematic content analysis. LHWs described a severe form of CMD amongst PLWH with a history of trauma, naming it kufungisisa kwe njodzi (excessive thinking due to trauma), a local cultural equivalent of PTSD. The term kufungisisa (thinking too much) has been used as the local equivalent for CMD. Trauma or njodzi was seen both as a circumscribed event and as linked to ongoing pervasive experiences such as living with HIV, stigma, and poverty. Although LHWs recognized symptoms of PTSD such as intrusion, avoidance, and hyper-arousal, they did not know how to address these specifically and chose to address them as a severe form of kufungisisa . There is a need to integrate aspects of PTSD management within care packages for CMD delivered by LHWs.